INTERCONDYLAR (Y) FRACTURE OF THE DISTAL HUMERUS IN A 8-YEAR-OLD CHILD - Todorovikj, Lazar; Kamiloski, Marjan; Memeti, Shaban; Mikjunovikj, Ljubica; Cokleska, Natalija; Aleksovski, Zlatko; Aleksovski, Goran (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
Intercondylar fracture of the distal humerus is an extremely rare injury in children, especially in those under 8 years of age. To our knowledge, there have been around 50 reported cases of this fracture type in children in the English literature, 12 of which involved children under 8 years of age. Keywords: child, humerus, intercondylar fracture, intercondylar Y fracture, intra-articular elbow fracture. https://doi.org/10.55302/JMS2143052t